A Crop of High Nutritional Quality and Health Maintenance Value: The Importance of Tartary Buckwheat Breeding - Ivan Kreft; Aleksandra Golob; Mateja Germ (Agriculture, 2023)
Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.), originating in the Himalayan area, is cultivated in central Asia and northern, central, and eastern Europe. Tartary buckwheat grain and sprouts are rich in flavonoid metabolites rutin and quercetin. The synthesis of flavonoids in plants is accelerated by UV-B solar radiation to protect the plants against radiation damage. During Tartary buckwheat food processing, a part of rutin is enzymatically converted to quercetin. Rutin and quercetin are able to pass the blood–brain barrier. Studies have investigated the effects of rutin and quercetin on blood flow to the brain, consequently bringing more nutrients and oxygen to the brain, and causing improved brain function. In addition to the impact on blood flow, rutin and quercetin have been shown to have antioxidative properties. The goals of breeding Tartary buckwheat are mainly to maintain and enhance the high nutritional quality. The goals could be reached via the breeding of Tartray buckwheat for larger cotyledons. Other main breeding efforts should be concentrated on the easy husking of the grain, the prevention of seed shattering, and the improvement in growth habits to obtain uniformity in grain ripening and a stable and high yield.